2019
DOI: 10.3201/eid2507.181492
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome and Antimicrobial Resistance Gene Dynamics in International Travelers

Abstract: We used metagenomic next-generation sequencing to longitudinally assess the gut microbiota and antimicrobial resistomes of international travelers to clarify global exchange of resistant organisms. Travel resulted in an increase in antimicrobial resistance genes and a greater proportion of Escherichia species within gut microbial communities without impacting diversity.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 14 publications
4
23
0
Order By: Relevance
“…Thus, ARGs may amplify or change genetic background within animal vectors, which may constitute a reservoir of antibiotic resistance. Humans are the most studied animal vector (e.g., [107,108]). Farmers and other workers in direct contact with livestock have been shown to develop increased resistance [109,110,111,112].…”
Section: An Overview Of Antibiotic Resistance In the Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, ARGs may amplify or change genetic background within animal vectors, which may constitute a reservoir of antibiotic resistance. Humans are the most studied animal vector (e.g., [107,108]). Farmers and other workers in direct contact with livestock have been shown to develop increased resistance [109,110,111,112].…”
Section: An Overview Of Antibiotic Resistance In the Environmentmentioning
confidence: 99%
“…In addition to health care, farm, and WWTP workers, the dissemination of ARBs has been connected to international travellers. Several studies have demonstrated that commensals and pathogens carrying ARGs can establish themselves in the travellers’ microbiome, and that these ARBs can persist for a length of time after return to the country of origin [107,108]. For example, Swedish students undergoing an exchange to India were significantly more likely to return home carrying E. coli with ESBL genes than those staying in Central Africa, and establishment of ARB strains in the students’ microbiomes occurred without any antibiotic treatment [107].…”
Section: An Overview Of Antibiotic Resistance In the Environmentmentioning
confidence: 99%
“…However, current knowledge on the link between the microbiome and MDRO colonisation is limited [ 12 , 13 ]. In travellers, an increase of antimicrobial resistance genes and Escherichia coli relative abundance in the microbiome were observed after acquisition and asymptomatic carriage of extended-spectrum beta-lactamase (ESBL)-producing E. coli , but without clear differences in microbial community structure [ 14 ]. An exception to the understudied role of the microbiome in MDRO colonisation is vancomycin-resistant Enteroccocus (VRE).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, this will have lessened the exposure to a range of external environmental microbiota. Pre-pandemic, international travellers had a higher proportion of Escherichia species and increased antimicrobial resistance genes ( 27 ). While it is known that travel is a modifying factor for the adult microbiome ( 28 ), we do not know the effect of an absence of travel on the microbiome.…”
Section: Indirect Effects Of Pandemic On An Individual or Populationsmentioning
confidence: 99%